Influence of the Angle of Cervical Convergence on Stresses to the PDL of Abutments: A 3D Analysis Using Finite Element Method - A. Geramy; Gh. Ommati-Shabestary; L. Eghlima (Frontiers in Dentistry, 2007)
Objective: This study was designed to compare the stress produced at the PDL of abutment teeth with two angles of cervical convergence, in otherwise similar settings.